First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2014)

A thinned lithosphere beneath coastal area of southeastern China as evidenced by seismic receiver functions - Zhuo Ye; QiuSheng Li; Rui Gao; HongShuang Zhang; RiZheng He; HaiYan Wang; WenHui Li (Science China Earth Sciences, 2014)

Arbuscular mycorrhizae improve low temperature tolerance in cucumber via alterations in H2O2 accumulation and ATPase activity - Airong Liu; Shuangchen Chen; Rui Chang; Dilin Liu; Haoran Chen; Golam Jalal Ahammed; Xiaomin Lin; Chaoxing He (Journal of Plant Research, 2014)

Characteristics of UV radiation at Tazhong of the Tarim Basin, west China - Lili Jin; Qing He; Zhenjie Li; Rui Liu; Ali Mamtimin; Qilong Miao (Meteorology and Atmospheric Physics, 2014)

Needle-free injection of insulin powder: delivery efficiency and skin irritation assessment - Chun-yu Li; Zhe-wei Wang; Can Tu; Jia-bo Wang; Bing-qian Jiang; Qi Li; Ling-na Zeng; Zhi-jie Ma; Ping Zhang; Yan-ling Zhao; Ya-ming Zhang; Dan Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Distance effect of matrix attachment regions on transgene expression in stably transfected Chinese hamster ovary cells - Jun-He Zhang; Xiao-Yin Wang; Tian-Yun Wang; Fang Wang; Wei-Hua Dong; Li Wang; Chun-Peng Zhao; Shu-Jie Chai; Rui Yang; Qin Li (Biotechnology Letters, 2014)

ORF005L from infectious spleen and kidney necrosis virus is located in the inner mitochondrial membrane and induces apoptosis - Rui Wang; Yang Yi; Lihong Liu; Yanghong Lu; Shaoping Weng; Jianguo He; Xiaopeng Xu (Virus Genes, 2014)

Effect of hepatic function on the EC50 of midazolam and the BIS50 at the time of loss of consciousness - Yu-hong Li; Rui He; Jin-guang Ruan (Journal of Zhejiang University-SCIENCE B, 2014)

Identification of a putative cognate sensor kinase for the two‐component response regulator HrpG , a key regulator controlling the expression of the hrp genes in X anthomonas campestris pv. campestris - Rui‐Fang Li; Guang‐Tao Lu; Lei Li; Hui‐Zhao Su; Guo‐fang Feng; Ya Chen; Yong‐Qiang He; Bo‐Le Jiang; Dong‐Jie Tang; Ji‐Liang Tang (Environmental Microbiology, 2014)
Summary The bacterial phytopathogen X anthomonas campestris pv. campestris ( Xcc ) relies on the hrp (hypersensitive response and pathogenicity) genes to cause disease and induce hypersensitive response ( HR ). The hrp genes of bacterial phytopathogens are divided into two groups. Xcc hrp genes belong to group II . It has long been known that the group II hrp genes are activated by an AraC ‐type transcriptional regulator whose expression is controlled by a two‐component system ( TCS ) response regulator (named HrpG in Xcc ). However, no cognate sensor kinase has yet been identified. Here, we present evidence showing that the Xcc open‐reading frame XC _3670 encodes a TCS sensor kinase (named HpaS ). Mutation of hpaS almost completely abolished the HR induction and virulence. Bacterial two‐hybrid and protein pull‐down assays revealed that HpaS physically interacted with HrpG . Phos‐tag™ SDS‐PAGE analysis showed that mutation in hpaS reduced markedly the phosphorylation of HrpG in vivo . These data suggest that HpaS and HrpG are most likely to form a TCS . We also showed that XC _3669 (named hpaR2 ), which is adjacent to hpaS and encodes a putative TCS response regulator, is required for full virulence but not HR induction. HpaR2 also physically interacted with HpaS , suggesting that HpaS may also form another TCS with HpaR2 .

Purification and photodynamic bioactivity of phycoerythrin and phycocyanin from Porphyra yezoensis Ueda - Chuner Cai; Yuan Wang; Chunxia Li; Ziye Guo; Rui Jia; Weining Wu; Yan Hu; Peimin He (Journal of Ocean University of China, 2014)

Down-regulated Six2 by knockdown of neurofibromin results in apoptosis of metanephric mesenchyme cells in vitro - Puhui Zhou; Tielin Chen; Yin Fang; Honglian Wang; Mi Li; Pengpeng Ma; Lu He; Qianyin Li; Tianming Liu; Xianggui Yang; Fang Nie; Xiaoyan Wang; et al. (Molecular and Cellular Biochemistry, 2014)

Detection of respiratory syncytial virus fusion protein variants between 2009 and 2012 in China - Qiuling Xia; Lili Zhou; Caijing Peng; Rui Hao; Ke Ni; Na Zang; Luo Ren; Yu Deng; Xiaohong Xie; Linli He; Daiyin Tian; Lijia Wang; et al. (Archives of Virology, 2014)

Catastrophe theory to assess water security and adaptation strategy in the context of environmental change - Wang Xiao-jun; Zhang Jian-yun; Shamsuddin Shahid; Xia Xing-hui; He Rui-min; Shang Man-ting (Mitigation and Adaptation Strategies for Global Change, 2014)

Mechanism and comprehensive countermeasure for drought management from the view of catastrophe theory - Xiao-jun Wang; Jian-yun Zhang; Xue-wei Tong; Shahid Shamsuddin; Rui-min He; Xing-hui Xia (Natural Hazards, 2014)

Spatial and temporal plasticity of synaptic organization in anterior cingulate cortex following peripheral inflammatory pain: multi-electrode array recordings in rats - Yun-Fei Lu; Yan Wang; Ying He; Fu-Kang Zhang; Ting He; Rui-Rui Wang; Xue-Feng Chen; Fei Yang; Ke-Rui Gong; Jun Chen (Neuroscience Bulletin, 2014)

Effects of vascular endothelial growth factor B on proliferation and migration in EA.Hy926 cells - Guang-hong Zhang; Rui Qin; Shui-hua Zhang; He Zhu (Molecular Biology Reports, 2014)

JNK Is Necessary for Oligodendrocyte Precursor Cell Proliferation Induced by the Conditioned Medium from B104 Neuroblastoma Cells - Jing-Xing Zhang; Yi-Fan Feng; Qi Qi; Lin Shen; Rui Wang; Jian-Sheng Zhou; He-Zuo Lü; Jian-Guo Hu (Journal of Molecular Neuroscience, 2014)

Climate change and water resources management in Tuwei river basin of Northwest China - Wang Xiao-jun; Zhang Jian-yun; Wang Jian-hua; He Rui-min; Amgad ElMahdi; Liu Jin-hua; Wang Xin-gong; David King; Shamsuddin Shahid (Mitigation and Adaptation Strategies for Global Change, 2014)